Developing a Two-Tier Proportional Reasoning Skill Test: Validity and Reliability Studies - Kübra Açıkgül (International Journal of Assessment Tools in Education)
The main aim of this study is to develop a useful, valid, and reliable two-tier proportional reasoning skill test for middle school 7th and 8th-grade students. The research was carried out using the sequential explanatory mixed method. The study group of this research comprised of 391 (n7th-grade= 223, n8th-grade= 168) students. With validity and reliability studies, the content, face, construct, discriminant validity, and reliability coefficient of the test were examined. As a result, the two-tier proportional reasoning skill test with 12 items under 3 factors (qualitative prediction and comparison, missing value, numerical comparison) valid and reliable for adequate values specified in the literature.